Romania : Integrated Water Resources Rapid Assessment - World Bank (Washington, DC, 2014)
The purpose of this report is to assess the climate change impacts on water resources in Romania from an integrated, multi-sectoral perspective, and to recommend priority actions for addressing the identified risks and opportunities. The analysis is presented from an integrated water resources perspective, thereby including all pertinent water-related sectors, viz. municipal water supply and sanitation, industrial water supply, agriculture, energy generation, environment, and disaster management. More details on specific water-related aspects can be found in the companion rapid assessment reports for the energy, urban, and agricultural and rural development sectors. The recommended priority actions are presented in the context of consideration for possible financing under the operational programs funded by the European Structural and Investment Funds (ESIF) in 2014-2020 planning horizon. This analysis is based on the available information on the current status of water resources sector in Romania, along with the existing knowledge on the anticipated impacts of climate change in this sector.